Subadventitial resection of the ureter—new method for surgical corrections of the ureteropelvic junction and ureterovesical junction obstructions - Akif Memmedoglu Bağirov (Asian Journal of Urology)
Objective: The aim of our study was to examine results of pyeloplasty using the new method—subadventitial resection of the ureter with preservation of the ureteral artery proposed by us and the possibility of using this method in one-stage surgery with ureteropelvic junction (UPJ) and ureterovesical junction (UVJ) obstructions or vesicoureteral reflux. Methods: A retrospective analysis of 108 patients with hydronephrosis (including two patients with hydroureteronephrosis) who received treatment from March 1998 to March 2020 was carried out, with an average follow-up period of 36 months. Dismembered pyeloplasty using a subadventitial technique with preservation of ureteral blood supply was performed in 108 patients (including bilateral in two cases). In one patient with UPJ and UVJ obstructions and in one patient with UPJ obstruction and vesicoureteral reflux subadventitial resection of the ureter were performed in both segments. Results: All patients managed to preserve the integrity of the ureteral artery during dismembered pyeloplasty, and two patients simultaneously underwent ureterocystostomy by subadventitial resection of the ureter. The method of pyeloureteroplasty with subadventitial resection of the ureter makes it possible to improve long-term results in patients with hydronephrosis, including those with lesions of the UPJ and UVJ segments. In all cases, it was feasible to achieve a decrease in the degree of hydronephrosis. Postoperative complications were observed in five cases (4.6%), in none of which there were complications associated with the surgical technique, and were eliminated without loss of renal function. Conclusion: Our 22 years of experience shows that the technique of subadventitial resection of the ureter allows us to preserve the ureteral blood circulation during dismembered pyeloplasty and thus creates conditions for prevention of restenosis of UPJ and for single-stage ureteroplasty on the upper and lower ureteral segments.